Lado Lado Lodo Sdn. Bhd - Lajlin, Diana; Misak, Cecilia; Saleh, Estephanie; Noriman, Mohd Khairul Faiz; Abdul Hadis, Nurul Shafiqah Anira (2014)
Our name of company is Lada Lado LodoSdn.Bhd. The name refer to our product namely Sambal Lada. Our companies locate in Membakut jaya, Beaufort Sabah. Our businesses are producing and supplier sambal lada. Sambal Lada (Malay language) is a ready eat fresh chili paste that mixed with variety of spice, our main ingredient for the Sambal Lada of course a fresh chili paste that have been mixed with spices like onion, garlic and other ingredient that include in making the Samba ILada. Our Sambal Lada can be eaten fresh as a dipping, or can be used for a base for frying rice and in other cooking dish. Nowadays, many people take a single action to just buy foods that have been already processed in the market because they do not have time to do their own at home.